Environmental Degradation of the Marshes and Its Impact on Livestock Rearing (Case Study: Hammar Marsh in Dhi Qar Province) - Ghat’a Khaji Al-Lami, Ibtisam ((Humanities, social and applied sciences) Misan Journal of Academic Studies, 2025)
This study examines the extent of environmental degradation in the Hammar Marsh and its impact on livestock in Dhi Qar Province. The study area is the Hammar Marsh depression, located within the administrative boundaries of Dhi Qar. It is considered one of the largest surface water depressions in Iraq, fed mainly by the Euphrates River in addition to waters flowing from the Qurna marshes. In general, the water supply sources of the Hammar Marsh vary depending on the morphological changes the marsh has undergone, meaning that the feeding channels have changed over time. The study reveals that the Hammar Marsh has undergone major environmental changes due to both natural and human factors. Natural factors include rising temperatures and reduced rainfall, while human factors involve the construction of dams, reservoirs, and irrigation projects on the Tigris and Euphrates, as well as drainage operations. These changes caused a clear environmental impact, shrinking the marsh by 56% of the total 1,750 km² in the province, and by 59.77% during the 1990s compared to the 1970s. The marsh has continued to shrink and dry up due to reduced water releases and climate change, with its area estimated at around 1,200 km² during 2022–2023, representing only 68% of its original area in Dhi Qar. This decline in water coverage also reduced the extent of wetlands and vegetation cover. In the 1970s, vegetation covered about 1,753 km², but this fell to 919 km² in the 1990s following drainage operations. As a result, dissolved salts (TDS) increased from 3,000–6,000 mg/L to 6,100–9,100 mg/L, while electrical conductivity (EC) values ranged from 9.35 to 15.11 dS/m, affected by changes in both water quantity and quality upstream of the Euphrates and human activity along its course. However, with the partial restoration of the marshes and increased water levels, vegetation expanded again to about 970 km². Any decline in livestock productivity is directly linked to the shrinking of the marshes and reduced water releases, since livestock depend primarily on natural vegetation, alongside other types of feed. The drop in water levels, changes in water quality, and increased salinity have led to animal deaths, with more than 700 animals lost. Livestock numbers varied across the area: buffalo numbered 26,500, with 1,062 fish ponds recorded, while cattle, sheep, goats, and camels reached 50,322; 32,227; 3,166; and 2,221 respectively. Meanwhile, the number of herders dropped to 7,432—representing 39% of the total in the province. DOI: https://doi.org/10.54633/2333-024-056-026